A New Generation of Smart Amine Donors for Transaminase‐Mediated Biotransformations. Issue 36 (3rd August 2016) - Gomm, Andrew; Lewis, William; Green, Anthony P.; O'Reilly, Elaine
Abstract: The application of ω‐transaminase biocatalysts for the synthesis of optically pure chiral amines presents a number of challenges, including difficulties associated with displacing the challenging reaction equilibria. Herein, we report a highly effective approach using low equivalents of the new diamine donor, cadaverine, which enables high conversions of challenging substrates to the corresponding chiral amines in excellent ee . This approach paves the way for the design of self‐sufficient fermentation processes combining transaminase biotransformations with existing strategies for cadaverine production by decarboxylation of endogenous lysine. Abstract : So smart ! ω‐Transaminase (ω‐TA) biocatalysts have been used in combination with a "smart" diamine donor, enabling the highly efficient preparation of optically pure chiral amines. This new‐generation donor is highly effective at displacing the challenging reaction equilibrium and significantly outperforms the widely used donor, isopropylamine.